Design of optimal reactive distillation processes for etbe production using rigorous thermodynamic models - Durruty, Gisela Noel (2014)
In this work we propose a model for the design of a reactive distillation unit for ETBE synthesis from ethanol and isobutene, with both rigorous thermodynamic models (UNIFAC and SRK) and hydraulic constraints, in an equation oriented environment within GAMS. The objective is to minimize total annual cost. The main contribution of this paper is the estimation of binary interaction parameters yet unavailable for the system being considered, using experimental data taken from literature, within a reactive distillation column optimization environment.